There are 3 questions in this calculation: for each question, the 4 derivative of x is calculated.
Note that variables are case sensitive.\[ \begin{equation}\begin{split}[1/3]Find\ the\ 4th\ derivative\ of\ function\ e^{x} - x - 1\ with\ respect\ to\ x:\\\end{split}\end{equation} \]
\[ \begin{equation}\begin{split}\\Solution:&\\ &\color{blue}{The\ first\ derivative\ function:}\\&\frac{d\left( e^{x} - x - 1\right)}{dx}\\=&e^{x} - 1 + 0\\=&e^{x} - 1\\\\ &\color{blue}{The\ second\ derivative\ of\ function:} \\&\frac{d\left( e^{x} - 1\right)}{dx}\\=&e^{x} + 0\\=&e^{x}\\\\ &\color{blue}{The\ third\ derivative\ of\ function:} \\&\frac{d\left( e^{x}\right)}{dx}\\=&e^{x}\\=&e^{x}\\\\ &\color{blue}{The\ 4th\ derivative\ of\ function:} \\&\frac{d\left( e^{x}\right)}{dx}\\=&e^{x}\\=&e^{x}\\ \end{split}\end{equation} \]\[ \begin{equation}\begin{split}[2/3]Find\ the\ 4th\ derivative\ of\ function\ x - 1 - ln(x)\ with\ respect\ to\ x:\\\end{split}\end{equation} \]
\[ \begin{equation}\begin{split}\\Solution:&\\ &Primitive\ function\ = x - ln(x) - 1\\&\color{blue}{The\ first\ derivative\ function:}\\&\frac{d\left( x - ln(x) - 1\right)}{dx}\\=&1 - \frac{1}{(x)} + 0\\=& - \frac{1}{x} + 1\\\\ &\color{blue}{The\ second\ derivative\ of\ function:} \\&\frac{d\left( - \frac{1}{x} + 1\right)}{dx}\\=& - \frac{-1}{x^{2}} + 0\\=&\frac{1}{x^{2}}\\\\ &\color{blue}{The\ third\ derivative\ of\ function:} \\&\frac{d\left( \frac{1}{x^{2}}\right)}{dx}\\=&\frac{-2}{x^{3}}\\\\ &\color{blue}{The\ 4th\ derivative\ of\ function:} \\&\frac{d\left( - \frac{2}{x^{3}}\right)}{dx}\\=& - \frac{2*-3}{x^{4}}\\=&\frac{6}{x^{4}}\\ \end{split}\end{equation} \]\[ \begin{equation}\begin{split}[3/3]Find\ the\ 4th\ derivative\ of\ function\ e^{x} - 2 - ln(x)\ with\ respect\ to\ x:\\\end{split}\end{equation} \]
\[ \begin{equation}\begin{split}\\Solution:&\\ &Primitive\ function\ = e^{x} - ln(x) - 2\\&\color{blue}{The\ first\ derivative\ function:}\\&\frac{d\left( e^{x} - ln(x) - 2\right)}{dx}\\=&e^{x} - \frac{1}{(x)} + 0\\=&e^{x} - \frac{1}{x}\\\\ &\color{blue}{The\ second\ derivative\ of\ function:} \\&\frac{d\left( e^{x} - \frac{1}{x}\right)}{dx}\\=&e^{x} - \frac{-1}{x^{2}}\\=&e^{x} + \frac{1}{x^{2}}\\\\ &\color{blue}{The\ third\ derivative\ of\ function:} \\&\frac{d\left( e^{x} + \frac{1}{x^{2}}\right)}{dx}\\=&e^{x} + \frac{-2}{x^{3}}\\=&e^{x} - \frac{2}{x^{3}}\\\\ &\color{blue}{The\ 4th\ derivative\ of\ function:} \\&\frac{d\left( e^{x} - \frac{2}{x^{3}}\right)}{dx}\\=&e^{x} - \frac{2*-3}{x^{4}}\\=&e^{x} + \frac{6}{x^{4}}\\ \end{split}\end{equation} \]Your problem has not been solved here? Please go to the Hot Problems section!